Frequency-invariant beamforming for circular arrays - Zhang, Xin (2011)
Sensor arrays have been used widely in applications including radar, sonar, seismology, biomedicine, communications, geophysical exploration, astronomy and imaging. A very popular type of sensor arrays is the circular array. It has several advantages such as the fact that it can perform 360o scan very conveniently and during the scan the gain response can be kept almost invariant. In this research study, we focused on the investigation and design of broadband beamforming techniques using circular arrays. Such techniques can perform speech acquisition and enhancement under noisy environments. Possible practical applications include video conferencing at boardrooms or hands-free communications in vehicular environments.